Nutritional Aspects in Patients with Head and Neck Cancer: A Pilot Study - dos-Santos, Laise Rodrigues; Dantas, Juliana Borges de Lima; Carrera, Manoela; Martins, Gabriela Botelho; Lima, Hayana Ramos; Ramos, Lílian Barbosa; Medrado, Alena Ribeiro Alves Peixoto (Journal of Oral Diagnosis, 2019)
Introduction: Individuals with cancer of the head and neck treated by surgery, radio- therapy, and/or chemotherapy may present signs and symptoms that directly influence nutritional status including anorexia, weight loss, fatigue, dysphagia, early satiety, xerostomia, nausea, and vomiting. Objective: To evaluate the ponderal evolution and the occurrence of signs and symptoms in head and neck cancer patients receiving radio- chemotherapy treatment. Material and Methods: Prospective research was conducted using a standardized form, semi structured questionnaire, and clinical chart. Weights were recorded for 1 month prior to treatment, and for each 6 sessions of radiotherapy, up to 24º. Signs and symptoms reported by patients during the treatment period were recorded. Results: Eighty-nine percent of the individuals were male. The rhinopharynx was the most affected region (32.14%), and 78.57% patients had a stage II or III disease. Significant weight loss (p> 0.001) was observed, and body mass index analysis revealed an increase in the percentage of leanness at the end of treatment (32.14%). No relationship was found between weight loss and the occurrence of signs and symptoms. Conclusions: Significant weight loss occurred during antineoplastic treatment. The importance of nutritional monitoring from the beginning of oncologic treatment is confirmed, in order to establish an adequate nutritional intervention aimed at providing better tolerance to treatment and improvement in patients’ quality of life.